A polysiloxane diamine monomer containing a side group, a preparation method thereof, and a preparation method and application of a silicon-containing polyimide varnish
Patent Information
- Application Number
- CN202611136645.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
[0012]针对如上技术问题,本发明提供一种含侧基的聚硅氧烷二胺单体及其制备方法和一种含硅聚酰亚胺清漆的制备方法及应用,解决了传统含硅聚酰亚胺清漆含固量低、粘度高、与铜基材附着力差等技术问题
(1)本发明合成了一种全新结构的侧链己基改性双端氨基含侧基的聚硅氧烷二胺单体,通过在聚硅氧烷侧链引入正己基,破坏了聚二甲基硅氧烷分子链的规整性,降低了分子链的堆砌密度,显著提高了聚硅氧烷在极性溶剂中的溶解度,制备的聚酰亚胺清漆固含量可达30%~35%。
Smart Images

Figure SMS_2 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a polysiloxane diamine monomer containing side groups and its preparation method, and a method for preparing a silicon-containing polyimide varnish. Background Technology
[0002] The rapid development of the new energy electric vehicle industry has placed increasingly higher demands on the performance of drive motors. As a core component of electric vehicles, the reliability of the drive motor's insulation system directly affects the safety and service life of the entire vehicle. Enameled wire is a key component of the motor's insulation system, and the performance of its insulation coating determines the motor's heat resistance, electrical performance, mechanical performance, and environmental resistance.
[0003] Polyimide (PI) is widely used as an insulating coating for motor enameled wires due to its excellent heat resistance, electrical insulation, mechanical properties, and chemical corrosion resistance. However, traditional aromatic polyimides suffer from problems such as poor solubility, poor melting, and poor processability due to their high molecular chain rigidity and strong intermolecular forces. They are typically only applied as polyamic acid precursors (i.e., polyimide varnishes) followed by imidization at high temperatures. Furthermore, traditional polyimides have poor adhesion to copper substrates, leading to coating peeling during motor operation and affecting the motor's insulation performance.
[0004] To improve the processing performance and adhesion of polyimides, researchers often introduce polysiloxane segments into the polyimide backbone to prepare silicon-containing polyimides. Polysiloxanes possess excellent flexibility, low surface energy, high and low temperature resistance, and weather resistance. Introducing them into the polyimide backbone can significantly improve their solubility, lower their glass transition temperature, and improve processing performance, while also enhancing their adhesion to the substrate.
[0005] Currently, the preparation of silicon-containing polyimides mainly adopts the diamine route, which involves first synthesizing polysiloxane diamine monomers with terminal amino groups and side groups, and then carrying out a polycondensation reaction with aromatic dianhydrides. Among them, terminal aminopropyl polydimethylsiloxane is the most commonly used silicon-containing diamine monomer. However, polydimethylsiloxane has poor compatibility with aromatic polyimides. When the polysiloxane content is high, phase separation easily occurs, leading to a decrease in the mechanical and electrical properties of the material. In addition, polydimethylsiloxane has strong hydrophobicity and limited solubility in polar solvents, resulting in polyimide varnishes with low solids content (usually 20%-30%) and high viscosity. Multiple coats are required to achieve the required insulation thickness during application, resulting in low production efficiency and the coating being prone to defects such as sagging and pinholes.
[0006] To address these issues, researchers have attempted to introduce different substituents, such as phenyl and trifluoropropyl, into the side chains of polysiloxanes to improve their compatibility with polyimides and polar solvents. For example, introducing phenyl groups can improve the heat resistance and compatibility with aromatic compounds of polysiloxanes, but it increases the rigidity of the molecular chain, reduces the flexibility of the polysiloxane, and phenyl-containing polysiloxanes are more expensive, hindering industrial production. Introducing trifluoropropyl groups can improve the oil resistance and dielectric properties of polysiloxanes, but this increases the cost of the material, and fluorinated compounds have certain environmental impacts.
[0007] Meanwhile, existing silicone-containing polyimide varnishes also have the following drawbacks: (1) Low solid content: In order to ensure that the varnish has a suitable coating viscosity, the solid content can usually only be controlled at 20-30%, which leads to an increase in the number of coatings, a decrease in production efficiency, and an increase in solvent evaporation, which increases VOC emissions and production costs.
[0008] (2) High viscosity: Under the same solid content, the polydimethylsiloxane modified polyimide solution has a higher viscosity, which is not conducive to high-speed coating production of enameled wire.
[0009] (3) Poor adhesion: The surface energy of polydimethylsiloxane segments is low, resulting in insufficient adhesion between the polyimide coating and the copper conductor. During motor operation, the coating is prone to peeling off, affecting the service life and reliability of the motor.
[0010] CN103748141A discloses a polyimide resin containing polysiloxane diamine residues. The core innovation of this patent lies in controlling the number of repeating units n (5~30) in the polysiloxane main chain to reduce the glass transition temperature of the resin to below 30°C to obtain room temperature adhesion. All its embodiments use only terminal aminopropyl polydimethylsiloxane with methyl side chains as the silane-containing diamine monomer. At the same time, this patent is aimed at the field of heat-resistant adhesives for electronic devices and does not address the specific technical problems faced by the clear varnish of enameled wires for new energy motors, such as low solids content, high viscosity, and poor adhesion to copper substrates.
[0011] Therefore, developing a novel silicon-containing diamine monomer that can improve the compatibility of polysiloxanes with polar solvents and polyimides, prepare high-solids-content, low-viscosity polyimide varnishes, and maintain excellent heat resistance, electrical properties, and adhesion is of great significance for the development of enameled wires for drive motors of new energy electric vehicles. Summary of the Invention
[0012] To address the above-mentioned technical problems, this invention provides a polysiloxane diamine monomer containing side groups and its preparation method, as well as a method for preparing and applying a silicon-containing polyimide varnish. This solves the technical problems of traditional silicon-containing polyimide varnishes, such as low solids content, high viscosity, and poor adhesion to copper substrates. The polyimide varnish prepared by this invention has advantages such as high solids content, moderate viscosity, good adhesion, excellent heat resistance, and stable electrical properties, making it particularly suitable for insulating coatings on enameled wires of drive motors in new energy electric vehicles.
[0013] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a polysiloxane diamine monomer containing side groups, having a molecular structure represented by the following general formula (I): (I) In formula (I), R is a C4-C18 alkyl group; n is an integer from 1 to 100, m is an integer from 1 to 200; and n / (n+m) = 0.1 to 0.9.
[0014] Furthermore, R is -(CH2)5CH3.
[0015] Secondly, the method for preparing the polysiloxane diamine monomer containing side groups according to the present invention includes the following steps: S1. Tetramethyltetrahydrocyclotetrasiloxane (D4H) was added to a reaction vessel, heated under nitrogen protection, and a platinum catalyst was added and stirred. 1-Hexene was added to the reaction system, and the reaction temperature was controlled during the dropwise addition. After the dropwise addition was completed, the reaction was kept at the temperature. After the reaction was completed, excess 1-hexene was removed by vacuum distillation to obtain tetrahexyltetramethylcyclotetrasiloxane. S2. The tetrahexyltetramethylcyclotetrasiloxane obtained in step S1, along with octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, are added to a reaction vessel and stirred until homogeneous under nitrogen protection. The mixture is then heated. A protic acid catalyst is added, and the temperature is raised to the reaction temperature and maintained for polymerization. After the reaction is complete, the temperature is lowered, a neutralizing agent is added, and the mixture is stirred to neutralize the reaction. The mixture is then filtered to remove the salt residue. The filtrate is distilled under reduced pressure to remove unreacted small molecule cyclosiloxanes, yielding a polysiloxane diamine monomer containing side groups.
[0016] The specific reaction synthesis route is shown below:
[0017] Further, in step S1, the platinum catalyst is either a Karstedt platinum catalyst or a Speier isopropanol chloroplatinate solution; when using a Karstedt platinum catalyst, the amount of platinum used is 1~15 ppm; when using a Speier isopropanol chloroplatinate solution, the amount of platinum used is 15~25 ppm. All amounts are based on the total mass of the reactants.
[0018] Further, in step S1, the molar ratio of tetramethyltetrahydrocyclotetrasiloxane to 1-hexene is 1:(4~5).
[0019] Furthermore, in step S1, the reaction temperature is controlled at 85~115℃ during the dropping process, and reflux can be used in conjunction with the dropping process.
[0020] Furthermore, in step S2, the protic acid catalyst is trifluoromethanesulfonic acid, concentrated sulfuric acid, or acidic clay; when using trifluoromethanesulfonic acid, the dosage is 0.05%~0.2%; when using concentrated sulfuric acid, the dosage is 0.2%~0.5%; and when using acidic clay, the dosage is 0.3%~0.8%. These catalyst dosage ranges ensure the reaction rate of the ring-opening polymerization while avoiding problems such as amino protonation, product yellowing, or chain segment degradation caused by excessive catalyst.
[0021] Furthermore, the neutralizing agent mentioned in step S2 is anhydrous sodium carbonate, sodium bicarbonate, or triethylamine; the pH value of the neutralized system is 6.5~7.5.
[0022] Furthermore, in step S2, the process conditions for vacuum distillation are 110~130℃, -0.097~-0.099MPa, and the vacuum distillation time is 2~5 hours.
[0023] Thirdly, the present invention provides a method for preparing a silicone-containing polyimide varnish, comprising the following steps: S1. Add the aromatic dianhydride monomer to an aprotic polar solvent, heat under nitrogen protection until completely dissolved, and cool to obtain a dianhydride solution; S2. Add the polysiloxane diamine monomer containing side groups prepared in this invention to the dianhydride solution obtained in step S1, stir and react to obtain an anhydride-terminated prepolymer solution. S3. Dissolve the aromatic diamine monomer in an aprotic polar solvent and add it dropwise to the prepolymer solution prepared in step (2). Stir the reaction to obtain a silicone polyamic acid polymer solution. S4. After the polyamic acid polymer solution containing silicone is allowed to stand to degas and is filtered to remove impurities, the finished polyamic acid varnish containing silicone is obtained.
[0024] Furthermore, the molar ratio of dianhydride monomer to total diamine monomer is (1.005~1.1); the side-chain hexyl-modified diamino-terminated polysiloxane diamine monomer accounts for 10%~70% of the total diamine monomer molarity. This invention achieves a precise balance of performance by controlling the molar ratio of side-chain hexyl-modified diamine to total diamine at 10%~70%: when the proportion is below 10%, the modification effect of the silicon-containing segments is not obvious, resulting in low solids content and poor adhesion in the varnish; when the proportion is above 70%, the proportion of rigid aromatic segments in the polyimide is insufficient, leading to a significant decrease in the material's heat resistance and mechanical strength, failing to meet the requirements for motor insulation.
[0025] Further, the aromatic dianhydride is selected from pyromellitic dianhydride (PMDA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), monoether tetracarboxylic dianhydride, 4,4'-(hexafluoropropylene)bisphthalic anhydride, 4,4'-bis( One or more of the following: 3,4-dicarboxyphenoxy)diphenyl ether dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride, 1,2,4,5-benzenetetracarboxylic acid dianhydride, 2,3,3',4'-benzophenone tetracarboxylic acid dianhydride, 2,2',6,6'-biphenyltetracarboxylic acid dianhydride, butane-1,2,3,4-tetracarboxylic acid dianhydride, cyclobutane-1,2,3,4-tetracarboxylic acid dianhydride, thiophene-2,3,4,5-tetracarboxylic acid dianhydride, and pyridine-2,3,5,6-tetracarboxylic acid dianhydride.
[0026] Further, the aromatic diamine is selected from one or more of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (p-PDA), m-phenylenediamine (m-PDA), 4,4'-diaminodiphenylmethane (DDM), 4,4'-diaminodiphenyl sulfone (DDS), o-diaminobenzene (o-PDA), 3,3'-dimethylbenzidine (TB), benzidine (BZ), m-phenylenediamine (MXDA), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-bis(3-aminophenoxy)biphenyl (m-BAPB), 2,6-diaminotoluene (2,6-DAT), and 2,4-diaminochlorobenzene:CDA.
[0027] Furthermore, the aprotic polar solvent is selected from one or more of N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N,N-dimethylacetamide (DMAc), and N,N-dimethylformamide (DMF).
[0028] Fourthly, the present invention provides an application of the prepared silicon-containing polyimide varnish in the insulation coating of the enameled wire of the drive motor of a new energy electric vehicle. Specifically, after being coated onto a metal wire, it is heated and imidized to transform it into a silicon-containing polyimide (PI) insulating varnish film.
[0029] The beneficial effects of this invention are as follows: (1) This invention synthesizes a novel polysiloxane diamine monomer with a side-chain hexyl-modified double-terminated amino group. By introducing n-hexyl groups into the side chain of polysiloxane, the regularity of the polydimethylsiloxane molecular chain is disrupted, the packing density of the molecular chain is reduced, and the solubility of polysiloxane in polar solvents is significantly improved. The solid content of the prepared polyimide varnish can reach 30%~35%.
[0030] (2) The polyimide varnish prepared by the present invention has a viscosity of 4000~6000 mPa·s at 25℃. The viscosity is moderate, the coating performance is good, and the required insulation thickness can be achieved in one coating, which significantly improves production efficiency.
[0031] (3) The introduction of hexyl groups in the side chain of this invention improves the adhesion between polyimide and copper substrate. This is because the introduction of hexyl groups in the side chain moderately reduces the regularity and crystallization tendency of the polysiloxane chain segments, so that the molecular chain can spread and wet more fully when in contact with the copper surface. At the same time, it reduces the thermal stress inside the coating, thereby significantly improving the adhesion. The adhesion reaches level 0, which solves the problem of easy peeling of traditional polyimide coatings and improves the reliability of motor insulation system.
[0032] (4) The preparation process of this invention is simple, eliminating the cumbersome steps of precipitation, drying and re-dissolution in the traditional process, and greatly reducing the cost of industrial production. Detailed Implementation
[0033] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions in the embodiments of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0034] Example 1 Example 1 provides a method for preparing a polysiloxane diamine monomer containing side groups, comprising the following steps: S1. In a flask equipped with a mechanical stirrer, thermometer, constant-pressure dropping funnel, and reflux condenser, add 480 g (2.0 mol) of tetramethyltetrahydrocyclotetrasiloxane, purge the air with nitrogen three times, and raise the temperature to 80°C. Add 0.96 g of Karstedt platinum catalyst (platinum content 2000 ppm, equivalent to 1.92 mg of platinum element, approximately 2 ppm of the total material mass), and stir to activate for 10 minutes. Then, slowly add 689 g (8.2 mol) of 1-hexene dropwise through the constant-pressure dropping funnel, controlling the reaction temperature at 95~105°C during the dropwise addition process, and the dropwise addition time is approximately 4 hours. After the dropwise addition is complete, maintain the reaction at 100°C for 6 hours. Take a sample for infrared spectroscopy analysis. When the 2160 cm⁻¹... -1 When the characteristic absorption peak of Si-H at the point completely disappears, it indicates that the reaction is complete.
[0035] The reaction solution was transferred to a rotary evaporator and distilled under reduced pressure at 90 °C and -0.097 MPa for 2 hours to remove excess 1-hexene, yielding 1068 g of a pale yellow transparent liquid, tetrahexyltetramethylcyclotetrasiloxane, with a yield of 96.2%.
[0036] ¹HNMR (CDCl3, 400MHz): δ0.05~0.15 (m,12H,Si-CH3), 0.50~0.60 (m,8H,Si-CH2-), 0.85~0.95 (t,12H,-CH3), 1.20~1.40 (m,32H,-CH2-).
[0037] S2. In a 1L three-necked flask equipped with a stirrer, thermometer, and nitrogen delivery tube, add 277.5g (0.5mol) of tetrahexyltetramethylcyclotetrasiloxane prepared in step S1, 148g (0.5mol) of octamethylcyclotetrasiloxane, and 24.8g (0.1mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane. The calculated n / (n+m) = 0.5. Purge the air with nitrogen three times, stir until homogeneous, and heat to 90℃. Add 0.45g of trifluoromethanesulfonic acid (0.1% of the total material mass), and heat to 110℃ for polymerization for 8 hours.
[0038] After the reaction was complete, the temperature was lowered to 70℃, and anhydrous sodium carbonate was added and stirred for 2 hours to neutralize. The pH of the system after neutralization was 7.0. The salt residue was removed by filtration, and the filtrate was transferred to a rotary evaporator and distilled under reduced pressure at 120℃ and -0.098 MPa for 3 hours to remove unreacted small-molecule cyclosiloxanes, yielding 392 g of a colorless, transparent, viscous liquid polysiloxane diamine monomer with hexyl-modified side-chain diamino groups, with a yield of 92.3%. GPC testing showed a number-average molecular weight (Mn) of 4200 and a molecular weight distribution (PDI) of 1.32. Amine titration showed a theoretical amine value of 26.7 mg KOH / g and a measured amine value of 26.2 mg KOH / g, which was basically consistent with the theoretical value.
[0039] Example 2 Example 2 provides a method for preparing a polysiloxane diamine monomer containing side groups. The difference from Example 1 is that in step S2, the amount of tetrahexyltetramethylcyclotetrasiloxane is 416.25 g (0.75 mol), and the amount of octamethylcyclotetrasiloxane is 74 g (0.25 mol). The remaining steps are the same, and the calculated n / (n+m) = 0.75. Example 2 yielded 458 g of a polysiloxane diamine monomer (DA-2) with hexyl-modified diamino groups at the ends of the side chain, with a yield of 93.1%. GPC testing showed: number-average molecular weight Mn = 4800, molecular weight distribution PDI = 1.35; amine titration showed: theoretical amine value of 23.3 mgKOH / g, and measured amine value of 22.9 mgKOH / g.
[0040] Example 3 Example 3 provides a method for preparing a silicone-containing polyimide varnish, comprising the following steps: S1. Preparation steps of dianhydride solution: In a three-necked flask equipped with a mechanical stirrer, thermometer and nitrogen delivery tube, add 27.27 g (0.053 mol) of 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA) and 100 g of N-methylpyrrolidone (NMP), and stir under nitrogen protection until completely dissolved to obtain dianhydride solution; S2. Prepolymerization reaction step: Dissolve 21.0 g (0.005 mol) of the diamine monomer prepared in Example 1 in 20 g NMP, and slowly add it dropwise to the above dianhydride solution. Control the reaction temperature at 5~10℃ and the dropwise addition time at about 30 min. After the dropwise addition is complete, continue stirring the reaction for 1.5 hours to obtain the terminal anhydride prepolymer solution. S3, Chain Extension Reaction Step: Dissolve 9.0 g (0.045 mol) of 4,4'-diaminodiphenyl ether (ODA) in 30 g of NMP (N-methylpyrrolidone), heat to 25 °C, and slowly add it dropwise to the prepolymer solution prepared in step S2 over approximately 1 hour. After the addition is complete, continue stirring for 8 hours to obtain a pale yellow, transparent polyamic acid-containing polymer solution. After the reaction is complete, cool the reaction solution and filter it through a 0.45 μm organic filter membrane to remove trace amounts of gel and mechanical impurities. Then, degas under a vacuum of -0.095 MPa for 30 minutes to obtain a polyimide varnish with a solid content of 32%.
[0041] Example 4 Example 4 provides a method for preparing a silicone-containing polyimide varnish. The difference between Example 4 and Example 3 is that the amount of diamine monomer used is 63.0 g (0.015 mol), and the amount of ODA used is 7.0 g (0.035 mol); the remaining steps are the same. Example 4 yields a silicone-containing polyimide varnish with a solid content of 33%.
[0042] Example 5 Example 5 provides a method for preparing a silicone-containing polyimide varnish. The difference between Example 5 and Example 3 is that the amount of diamine monomer used is 105.0 g (0.025 mol), and the amount of ODA used is 5.0 g (0.025 mol), while the other steps are the same. A side-chain hexyl-modified silicone-containing polyimide varnish with a solid content of 34% is obtained.
[0043] Example 6 Example 6 provides a method for preparing a silicone-containing polyimide varnish. The difference between Example 6 and Example 3 is that the amount of diamine monomer used is 147.0 g (0.035 mol), and the amount of ODA used is 3.0 g (0.015 mol), while the other steps are the same. A side-chain hexyl-modified silicone-containing polyimide varnish with a solid content of 35% is obtained.
[0044] Example 7 Example 7 provides a method for preparing a silicone-containing polyimide varnish. The difference between Example 7 and Example 3 is that the dianhydride used is 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), and the amount used is 16.76 g (0.052 mol). The remaining steps are the same. A side-chain hexyl-modified silicone-containing polyimide varnish with a solid content of 31% is obtained.
[0045] Comparative Example 1 Comparative Example 1 is a traditional preparation of silicone-containing polyimide varnish. The difference between Comparative Example 1 and Example 3 is that the silicone diamine monomer used is commercially available terminal aminopropyl polydimethylsiloxane (with unbranched methyl groups on the silicon and a number average molecular weight Mn=4000), and the amount used is 20.0g (0.005mol). The other steps are the same.
[0046] Due to the poor compatibility between polydimethylsiloxane and NMP, slight turbidity appears during the prepolymerization stage, and the turbidity intensifies after the chain extension reaction. The final varnish can only reach a maximum solid content of 22%. If the concentration exceeds this, layering and gelation will occur.
[0047] Comparative Example 2 The difference between Comparative Example 2 and Example 3 is that the amount of diamine monomer used was 4.2 g (0.001 mol), the amount of ODA used was 9.8 g (0.049 mol), the total molar amount of diamine was 0.05 mol, and the proportion of diamine monomer was 2% (below the lower limit of 10%). The remaining steps were the same. The resulting varnish had a solid content of only 24% and an adhesion rating of 2 on copper substrates, which did not meet the requirements for motor insulation.
[0048] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that the amount of diamine monomer used is 189.0 g (0.045 mol), the amount of ODA used is 1.0 g (0.005 mol), the total molar amount of diamine is 0.05 mol, and the proportion of diamine monomer is 90% (higher than the upper limit of 70%). The remaining steps are the same. Although the obtained varnish has a solid content of up to 36%, its thermal decomposition temperature is only 382°C, which is insufficient for heat resistance and cannot meet the high-temperature requirements of motors.
[0049] Performance testing The solid content, viscosity, and appearance of the polyimide varnishes prepared in Examples 3-7 and Comparative Examples 1-3 were tested. The varnishes prepared in Examples 3-7 and Comparative Examples 1-3 were uniformly coated onto the surface of the conductors using either mold coating or felt coating methods. They were then placed in a multi-temperature zone oven for solvent removal at 100-180°C and in-situ thermal imidization curing at 220-350°C. The coating-baking process was repeated until the film reached the target thickness. The adhesion and thermal decomposition temperature of the resulting polyimide film were tested. The test results are shown in Table 1.
[0050] Table 1. Test results of polyimide varnish and coating properties.
[0051] Molar ratio of silanine diamine to total diamine (%) Feeding calculation 10 30 50 70 30 10 2 90 Solid content (%) GB / T1725-2007 32 33 34 35 31 22 24 36 Viscosity (25℃, mPa·s) GB / T1723-1993 4120 4250 4480 5100 4080 7100 4950 4520 Appearance Visual observation transparent transparent transparent transparent transparent Slightly turbid transparent transparent Adhesion (copper substrate, grade) GB / T9286-1998 0 0 0 0 0 2 2 0 Thermal decomposition temperature (Td5%, ℃) <![CDATA[TGA, N₂ atmosphere, 10°C / min]]> 426 418 409 402 413 425 432 382 The test results in Table 1 show that: The polyimide varnishes prepared in Examples 3-7 of this invention (containing 10%-70% silanediamine) are all homogeneous transparent solutions with a solid content of 31%-35%, which is much higher than 22% in Comparative Example 1 (traditional methyl modification) and 24% in Comparative Example 2 (too low content). This indicates that the introduction of hexyl groups on the side chain significantly improves the solubility of polysiloxanes in polar solvents.
[0052] When the proportion of silanediamine is less than 10% (Comparative Example 2), the modification effect is not obvious, the solid content of the varnish is low and the adhesion is poor; when the proportion is higher than 70% (Comparative Example 3), although the solid content is further increased, the thermal decomposition temperature drops significantly and cannot meet the high temperature and insulation requirements of the motor.
[0053] The polyimide varnish prepared by this invention has a viscosity of 4000~6000 mPa·s at 25℃, which is moderate and provides good coating performance. The adhesion of the polyimide varnish prepared by this invention to copper substrates reaches grade 0, far superior to grade 2 of Comparative Examples 1 and 2, indicating that the introduction of the hexyl group significantly improves the bonding force between polyimide and copper substrates. Although Comparative Example 3 also has an adhesion grade of 0, its thermal decomposition temperature is significantly lower, failing to meet the application requirements. The polyimide varnish prepared by this invention maintains excellent heat resistance and electrical properties, with thermal decomposition temperatures all above 402℃, meeting the application requirements of drive motors for new energy electric vehicles.
[0054] Although the present invention has been described in detail by way of preferred embodiments, the present invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention.
Claims
1. A polysiloxane diamine monomer containing side groups, characterized in that, It has the molecular structure shown in the following general formula (I): (I) In formula (I), R is a C4-C18 alkyl group; n is an integer from 1 to 100, m is an integer from 1 to 200; and n / (n+m) = 0.1 to 0.
9.
2. The polysiloxane diamine monomer containing side groups as described in claim 1, characterized in that, R is -(CH2)5CH3.
3. A method for preparing the polysiloxane diamine monomer containing side groups as described in claim 2, characterized in that, Includes the following steps: S1. Tetramethyltetrahydrocyclotetrasiloxane was added to a reaction vessel, heated under nitrogen protection, and a platinum catalyst was added and stirred. 1-Hexene was added to the reaction system, and the reaction temperature was controlled during the dropwise addition. After the dropwise addition was completed, the reaction was kept at the temperature. After the reaction was completed, excess 1-hexene was removed by vacuum distillation to obtain tetrahexyltetramethylcyclotetrasiloxane. S2. The tetrahexyltetramethylcyclotetrasiloxane obtained in step S1, along with octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)tetramethyldisiloxane, are added to a reaction vessel and stirred until homogeneous under nitrogen protection. The mixture is then heated. A protic acid catalyst is added, and the temperature is raised to the reaction temperature and maintained for polymerization. After the reaction is complete, the temperature is lowered, a neutralizing agent is added, and the mixture is stirred to neutralize the reaction. The residue is removed by filtration. The filtrate is distilled under reduced pressure to remove unreacted small molecule cyclosiloxanes, yielding a polysiloxane diamine monomer containing side groups.
4. The method for preparing the polysiloxane diamine monomer containing side groups as described in claim 3, characterized in that, In step S1, the platinum catalyst is either Karstedt platinum catalyst or Speier isopropanol chloroplatinate solution; when using Karstedt platinum catalyst, the amount of platinum is 1~15 ppm; when using Speier isopropanol chloroplatinate solution, the amount of platinum is 15~25 ppm; in step S1, the molar ratio of tetramethyltetrahydrocyclotetrasiloxane to 1-hexene is 1:(4~5), and the reaction temperature is controlled at 85~115℃ during the dropwise addition process.
5. The method for preparing the polysiloxane diamine monomer containing side groups as described in claim 3, characterized in that, In step S2, the protic acid catalyst is trifluoromethanesulfonic acid, concentrated sulfuric acid, or acidic clay. When trifluoromethanesulfonic acid is used, the amount is 0.05% to 0.2%; when concentrated sulfuric acid is used, the amount is 0.2% to 0.5%; and when acidic clay is used, the amount is 0.3% to 0.8%.
6. A method for preparing a silicone-containing polyimide varnish, characterized in that, Includes the following steps: S1. Add the aromatic dianhydride monomer to an aprotic polar solvent, heat under nitrogen protection until completely dissolved, and cool to obtain a dianhydride solution; S2. Add the polysiloxane diamine monomer containing side groups as described in claim 2 to the dianhydride solution obtained in step S1, stir and react to obtain an anhydride-terminated prepolymer solution. S3. Dissolve the aromatic diamine monomer in an aprotic polar solvent and add it dropwise to the prepolymer solution prepared in step (2). Stir the reaction to obtain a silicone polyamic acid polymer solution. S4. After the polyamic acid polymer solution containing silicone is allowed to stand to degas and is filtered to remove impurities, the finished polyamic acid varnish containing silicone is obtained.
7. The method for preparing the silicone-containing polyimide varnish as described in claim 6, characterized in that, The molar ratio of dianhydride monomer to total diamine monomer is (1.005~1.1); the side-chain hexyl-modified diamino-terminated polysiloxane diamine monomer accounts for 10%~70% of the total diamine monomer molar amount.
8. The method for preparing the silicone-containing polyimide varnish as described in claim 6, characterized in that, Aromatic dianhydrides are selected from pyromellitic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, monoether tetracarboxylic dianhydride, 4,4'-(hexafluoropropylene)bisphthalic anhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl ether dianhydride, and 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide. The dihydride is selected from one or more of the following: 1,2,4,5-benzenetetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, 2,2',6,6'-biphenyltetracarboxylic dianhydride, butane-1,2,3,4-tetracarboxylic dianhydride, cyclobutane-1,2,3,4-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, and pyridine-2,3,5,6-tetracarboxylic dianhydride; the aromatic diamine is selected from 4,4'-diaminodiphenyl ether, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, and 4,4'- One or more of the following: diaminodiphenyl sulfone, o-diaminobenzene, 3,3'-dimethylbenzidine, benzidine, m-phenylenediamine, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 2,6-diaminotoluene, and 2,4-diaminochlorobenzene (CDA).
9. The method for preparing the silicone-containing polyimide varnish as described in claim 6, characterized in that, In step S3, the aprotic polar solvent is selected from one or more of N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide.
10. The application of the silicone-containing polyimide varnish prepared according to any one of claims 6-9 in the insulation coating of the enameled wire of the drive motor of a new energy electric vehicle.
Citation Information
Patent Citations
Polyimide resin, resin composition and laminated film using same
CN103748141A